Pengaruh Model Pembelajaran Blended Learning Terhadap Kemampuan Berpikir Kritis Matematika Siswa SMP Negeri 1 Lahewa Timur - Abi Rahmad Zalukhu; Netti Kariani Mendrofa; Yakin Niat Telaumbanua; Sadiana Lase (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
This study was grounded in preliminary observations conducted at SMP Negeri 1 Lahewa Timur, which revealed two major issues: (1) classroom instruction was predominantly delivered through conventional teaching methods, and (2) students’ critical thinking skills remained relatively low. In response to these challenges, the present study aimed to examine the effect of a blended learning model on students’ critical thinking ability. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The population comprised all eighth-grade students, with two intact classes selected as the sample through total sampling: Class VIII-A served as the experimental group, while Class VIII-B functioned as the control group. The research instrument consisted of essay-type tests administered as both pre-test and post-test to measure students’ critical thinking skills. The results indicated a substantial improvement in the experimental group following the implementation of blended learning. The mean pre-test scores were 30.44 for the experimental class and 28.35 for the control class. After the intervention, the mean post-test scores increased to 77.73 in the experimental class and 56.04 in the control class, demonstrating a notable gain in learning outcomes. Hypothesis testing using the t-test revealed that exceeded (7.476 > 1.708), leading to the rejection of H₀ and acceptance of H₁. In conclusion, the findings provide empirical evidence that the blended learning model has a significant positive effect on students’ critical thinking skills.